Life History Effects Linked to an Advantage for wAu Wolbachia in Drosophila - Cao, Li-Jun (Insects, 2019)
Wolbachia endosymbiont infections can persist and spread in insect populations without causing apparent effects on reproduction of their insect hosts, but the mechanisms involved are largely unknown. Here, we test for fitness effects of the wAu infection of Drosophila simulans by comparing multiple infected and uninfected polymorphic isofemale lines derived from nature. We show a fitness advantage (higher offspring number) for lines with the wAu Wolbachia infection when breeding on grapes, but only where there was Talaromyces and Penicillium fungal mycelial growth. When breeding on laboratory medium, the wAu infection extended the development time and resulted in larger females with higher fecundity, life history traits, which may increase fitness. A chemical associated with the fungi (ochratoxin A) did not specifically alter the fitness of wAu-infected larvae, which developed slower and emerged with a greater weight regardless of toxin levels. These findings suggest that the fitness benefits of Wolbachia in natural populations may reflect life history changes that are advantageous under particular circumstances, such as when breeding occurs in rotting fruit covered by abundant mycelial growth.